2007
DOI: 10.1562/2006-08-08-ra-1000
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Photophysical Behavior of Fisetin in Homogeneous Media and in Anionic and Cationic Reverse Micelles Media†

Abstract: The 3,3', 4',7 tetrahydroxiflavone (fisetin) is a natural therapeutically active and fluorescent polyhydroxyflavone, with important spectroscopic and biological behavior. Fisetin shows dual emission, with a normal band (N) from the S1 --> S0 transition and the one generated in the excited state (phototautomer; PT) from the intramolecular proton transfer (ESIPT) process. The influence of different interfaces on the ESIPT process of fisetin was investigated in reverse micelles media (RMs) made of the anionic sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…18,19 So far, there has been just one report of emission peak at this region and it is assigned to the anion form of fisetin in the homogeneous medium. 6 Further evidence was obtained from a methanolic solution of fisetin in 0.1 M sodium methoxide, showing excitation peak at 414 nm and corresponding emission peak at 490 nm. Thus the peak observed at 490 nm (l ex 418 nm) in NaC is due to the emission of (FA) GS .…”
Section: Photophysical Behavior Of Fisetin In Sodium Cholate Aggregatesmentioning
confidence: 96%
See 3 more Smart Citations
“…18,19 So far, there has been just one report of emission peak at this region and it is assigned to the anion form of fisetin in the homogeneous medium. 6 Further evidence was obtained from a methanolic solution of fisetin in 0.1 M sodium methoxide, showing excitation peak at 414 nm and corresponding emission peak at 490 nm. Thus the peak observed at 490 nm (l ex 418 nm) in NaC is due to the emission of (FA) GS .…”
Section: Photophysical Behavior Of Fisetin In Sodium Cholate Aggregatesmentioning
confidence: 96%
“…19 Moreover the excited state phototautomer does form by intramolecular proton transfer from this hydroxyl group. 6 Upon excitation at their characteristic wavelengths, FN species (l ex 369 nm) gives rise to FT, (FA*) ES and FN emission species, whereas the (FA) GS (l ex 418 nm) gives rise to (FA*) GS and FT emission. Scheme 1 also describes the prototropic equilibria of the various forms in the excited state, which leads to the highly overlaid emission spectra of FN and (FA) GS and hence there is no clear description of the emission peaks to each of the prototropic forms.…”
Section: Photophysical Behavior Of Fisetin In Sodium Cholate Aggregatesmentioning
confidence: 99%
See 2 more Smart Citations
“…6 This was confirmed also with the help of deuteration effects and it was found that ESIPT can even occur under cryogenic conditions via a tunneling mechanism 7 or in semi-biological environments. [8][9][10][11] Besides experimental work, effort has also been put into the theoretical description of excited states of biomolecular chromophores. 12,13,[18][19][20][21][22][23][24] We use densityfunctional theory (DFT) and time-dependent density functional theory (TDDFT) as efficient semi-quantitative methods to investigate the fluorescence emission behavior.…”
Section: Introductionmentioning
confidence: 99%